37. Notes on A Catalog of Difference - Andrew Lucia (Meta-Xenakis: New Perspectives on Iannis Xenakis’s Life, Work, and Legacies, 2024)
This chapter focuses on the author’s decade-long research project, A Catalog of Difference (2017). Approached from a background in architecture and art, this inquiry into spatial-material perception and its representation synthesizes information theoretic methodologies and concepts derived from Iannis Xenakis, Gregory Bateson, and the perceptual psychologist James J. Gibson, giving priority to an informational approach over that of the geometric. Architecture, through its representational tools and design workflows, has historically favored the latter of these distinctions, giving primacy to line and geometry at the expense of material phenomena. The work presented here challenges this bias while deliberately paying favor to formal potentials inherent within differentials of ambient light and surface curvatures. A Catalog of Difference is a study of change across material and perceptual environments, calling attention to those differences which make a difference. The collection comprises over 1,000 studies that survey and analyze degrees of difference across images, objects, and environments. The outcome of these studies is a collection of artifacts comprising a range of representation and media types including 3D printed ceramics, digital photography, renderings, and drawings. The difference machines elaborated on in the catalog operate as a methodology and collection of post-digital representations. The research is divided into three distinct yet related subsets examining the order and organization of: a) Planar ambient light, b) Surface curvatures, and c) Spherical ambient light. The studies in each of these questions form versus appearance.